2020
DOI: 10.1007/s10933-020-00116-2
|View full text |Cite
|
Sign up to set email alerts
|

The recent deposition of laminated sediments in highly eutrophic Lake Kierskie, western Poland: 1 year pilot study of limnological monitoring and sediment traps

Abstract: Accurate lake sediment-derived palaeoenvironmental reconstructions require in-depth knowledge on sediment record formation processes. In order to understand formation of laminated sediments in the eutrophic Lake Kierskie (western Poland) we conducted a year-round (November 2015-October 2016), monthly sediment trap study along with physicochemical water properties, water transparency, hardness, alkalinity, nutrients and solute content, trophic state indices, and the phytoplankton assemblage monitoring. Sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Such an interpretation is further supported by the present-day characteristics of Lake Spore waters in terms of Ca concentration and pH, the latter being another crucial variable controlling CaCO 3 precipitation within lakes (Kelts and Hsü, 1978). Although the pH value in the lake (~8; Jańczak, 1996; Pleskot et al, 2019) is similar to that reported in Polish lakes within which abundant deposition of CaCO 3 occurs at present (Apolinarska et al, 2020; Bonk et al, 2015), the concentration of Ca (<34 mg L −1 ; Jańczak, 1996) is two times smaller than that in other Polish lakes, suggesting it to be the main limiting factor for calcite precipitation within Lake Spore.…”
Section: Discussionsupporting
confidence: 74%
“…Such an interpretation is further supported by the present-day characteristics of Lake Spore waters in terms of Ca concentration and pH, the latter being another crucial variable controlling CaCO 3 precipitation within lakes (Kelts and Hsü, 1978). Although the pH value in the lake (~8; Jańczak, 1996; Pleskot et al, 2019) is similar to that reported in Polish lakes within which abundant deposition of CaCO 3 occurs at present (Apolinarska et al, 2020; Bonk et al, 2015), the concentration of Ca (<34 mg L −1 ; Jańczak, 1996) is two times smaller than that in other Polish lakes, suggesting it to be the main limiting factor for calcite precipitation within Lake Spore.…”
Section: Discussionsupporting
confidence: 74%
“…The sediment samples (upper 4 cm) which were used to assess sedimentary species composition of Cladocera and diatoms were also taken from the deepest part of the lake, alike the water sample, using Limnos sediment corer. The deepest point is regarded as representative for the whole lake for limnological and paleolimnological studies (Apolinarska et al, 2020;Davidson et al, 2010;Frey, 1988;Heggen et al, 2012;Tylmann et al, 2012). In case of a few lakes of complex morphology (Lake Ełckie, Żabińskie, Łazduny, Kamenduł, Kortowskie, Szurpiły, Dmitrowo, Długie), the bottom sediments were sampled in second deepest site.…”
Section: Methodsmentioning
confidence: 99%
“…The selection of 1 m depth as a representation of surface water followed the methodology of Tandyrak et al (2020). The deepest point is routinely regarded as representative for the whole lake (Tylmann et al 2012, Hernández-Almeida et al 2017, Apolinarska et al 2020. Chemical analysis of P tot ,(µgL −1 ) was done within a few days after collecting.…”
Section: Variables Lake Water Sampling and Determination Of P Totmentioning
confidence: 99%